The managerial perspective on influx of foreign workers in construction companies in Pahang - Rosezaimee, Abdullah @ Ismail (2015)
The construction sector is one of the key component that driving the Malaysia‟s economic growth and also the development for the nation. The construction sector can be categorises as labour-intensive businesses and the rapid expansion of the construction sectors creates a large number of employments in the country. But as there is a great scarcity of domestic labour force in the country, they have to depend largely on the migrant workers. The involvement of the foreign workers in constructions sector is increasing from time to time and have pose some positive and negative impact either directly or indirectly on the social balance in Pahang state.